Prevalence and Characteristics of Gastrointestinal Symptoms and Hepatic Manifestation in Covid-19 Infection in Tertiary Care Center - Khadka, Dipendra; KC, Sudhamshu; Regmi, Kiran; Bhandari, Binus (Journal of Nepalgunj Medical College, 2021)
Introduction: Although the primary clinical manifestation of COVID-19 is pulmonary disease, but there are increasing data to support the gastrointestinal and hepatic involvement. Aims: We aimed to see the prevalence and characteristics of gastrointestinal symptoms and hepatic manifestation in COVID-19 infection. Methods: This is a hospital based descriptive cross-sectional study which was carried out in medicine department of Nepalgunj Medical College. Consecutive patients of COVID-19 cases confirmed by polymerase chain reaction were included. The presenting complaints, laboratory parameters, clinical events were noted. The primary objective was to determine the prevalence of gastrointestinal manifestation and hepatic dysfunction and their correlation with severity of pneumonia. Results: Total patients enrolled in the study were 205. Majority of patients presented with respiratory symptoms 67.8%. Both respiratory and gastrointestinal symptoms were observed in 29.3% cases. Isolated gastrointestinal symptoms were observed in 2.9% cases. Common gastrointestinal symptoms were anorexia 14.1%, anorexia and nausea in 6.3%, pain abdomen in 3.9% and diarrhea in 2.4% cases. Hepatocellular type hepatic dysfunction reported in 53.2% cases. Rise in alanine aminotransferase (58.2% vs. 23.6%), aspartate aminotransferase (51.6% vs. 20.6%), alkaline phosphatase (44% vs. 15%), total bilirubin (76.6% vs12.5%) found significantly high in severe pneumonias compared with pneumonia only. Both gastrointestinal and hepatic dysfunctions were more common in severe cases (87.9% and 58.7%) than in mild disease (1% and 27%). Conclusion: One third of the patients of COVID-19 can have gastrointestinal symptoms and hepatic dysfunction. Around 3% of patients presented with isolated gastrointestinal symptoms. Thus, unexplained gastrointestinal symptoms in contacts of COVID-19 may demand polymerase chain reaction test to confirm the disease. Both gastrointestinal and hepatic dysfunction was more prevalent in severe pneumonia.